Anode active material layer and solid secondary battery

By using silicon active material particles with low oxygen content and small solid electrolyte particles, the negative electrode active material layer maintains stable conductivity and reduces resistance, addressing the expansion issues of silicon particles in batteries.

JP7616264B2Active Publication Date: 2025-01-17TOYOTA JIDOSHA KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023061781
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-04-05
Publication Date
2025-01-17
Estimated Expiration
2043-04-05

AI Technical Summary

Technical Problem

Silicon active material particles in negative electrodes expand greatly during charging, leading to increased electrical resistance due to deteriorated contact states between particles, particularly when the atomic weight of silicon is low.

Method used

The negative electrode active material layer is composed of silicon active material particles with less than 5.0% oxygen by mass and solid electrolyte particles with an average size of 1.0 μm or less, and/or a particle size ratio of 0.9 or less, to improve electrical conductivity and reduce resistance.

Benefits of technology

The solution enhances the electrical conductivity of silicon active material particles, maintaining a stable negative electrode layer with reduced electrical resistance even at low charging states.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616264000002
    Figure 0007616264000002
  • Figure 0007616264000003
    Figure 0007616264000003
  • Figure 0007616264000001
    Figure 0007616264000001
Patent Text Reader

Abstract

To provide a negative electrode active material layer that improves the electrical conductivity of silicon active material particles by reducing the amount of oxygen atoms in the silicon active material particles, while preventing the electrical resistance from deteriorating even when the charge capacity of the battery is low (=low charge state), and a solid secondary battery having such a negative electrode active material layer.SOLUTION: A negative electrode active material layer according to the present disclosure contains silicon active material particles and solid electrolyte particles, and the amount of oxygen atoms in the silicon active material particles is less than 5.0 mass%, and the average particle size of the solid electrolyte particles is 1.0 μm or less, and / or the ratio of the average particle size of the solid electrolyte particles to the average particle size of the silicon active material particles is 0.9 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a negative electrode active material layer and a solid secondary battery. [Background technology]

[0002] In recent years, the development of batteries has been actively carried out. For example, in the automobile industry, development of batteries for use in electric vehicles or hybrid vehicles is underway. Silicon is known as an active material for batteries.

[0003] Silicon active materials have a large theoretical capacity and are effective in increasing the energy density of batteries. On the other hand, silicon active materials have a problem of large expansion during charging. It is known that the expansion during charging can be suppressed by using a silicon clathrate active material as the silicon active material.

[0004] For example, Patent Document 1 discloses an all-solid-state battery in which a positive electrode layer, a solid electrolyte layer, and a negative electrode layer are laminated in this order, the negative electrode layer contains a negative electrode active material having a silicon clathrate II type crystal phase, the all-solid-state battery is applied with a confining pressure of 0 MPa or more and less than 5 MPa in the lamination direction, and when the capacity ratio of the negative electrode capacity to the positive electrode capacity is defined as A, the capacity ratio A is 2.5 or more and 4.8 or less.

[0005] Patent Document 2 describes an all-solid-state battery in which a positive electrode layer, a solid electrolyte layer, and a negative electrode layer are laminated in this order, the negative electrode layer contains a negative electrode active material having a silicon clathrate II type crystal phase, the all-solid-state battery is applied with a confining pressure of 0 MPa or more and less than 5 MPa in the lamination direction, and the specific surface area of ​​the negative electrode active material is 8 m 2 g or more 17m 2 / g or less. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent Publication No. 2022-092723 [Patent Document 2] Patent Publication No. 2022-092725 Summary of the Invention [Problem to be solved by the invention]

[0007] As described above, silicon active material particles expand greatly during charging, and therefore contract greatly during discharging. Therefore, in a negative electrode active material containing silicon active material particles, the silicon active material particles contract during discharging, which deteriorates the contact state between the particles constituting the negative electrode active material layer, and the electrical resistance of the negative electrode active material layer increases. In this regard, the present inventors have found that this problem is significant when the atomic weight of the silicon active material particles is small, and that such a problem can be suppressed by using solid electrolyte particles with a small particle size.

[0008] Therefore, an object of the present disclosure is to provide an anode active material layer in which the electrical conductivity of the silicon active material particles is improved by reducing the amount of oxygen atoms in the silicon active material particles, while the electrical resistance is not easily deteriorated even when the charge capacity of the battery is low (=low charge state), and a solid secondary battery having such an anode active material layer. [Means for solving the problem]

[0009] The present inventors have found that the above problems can be solved by the following means. <Aspect 1> Contains silicon active material particles and solid electrolyte particles, The amount of oxygen atoms in the silicon active material particles is less than 5.0% by mass, and the solid electrolyte particles have an average particle size of 1.0 μm or less, and / or the ratio of the average particle size of the solid electrolyte particles to the average particle size of the silicon active material particles is 0.9 or less; Negative electrode active material layer. <Aspect 2> 2. The negative electrode active material layer according to aspect 1, wherein the solid electrolyte particles have an average particle size of 1.0 μm or less. <Aspect 3> 3. The negative electrode active material layer according to aspect 2, wherein the solid electrolyte particles have an average particle size of 0.01 μm or more and 0.5 μm or less. <Aspect 4> 2. The negative electrode active material layer according to aspect 1, wherein a ratio of an average particle size of the solid electrolyte particles to an average particle size of the silicon active material particles is 0.9 or less. <Aspect 5> 5. The negative electrode active material layer according to aspect 4, wherein a ratio of an average particle size of the solid electrolyte particles to an average particle size of the silicon active material particles is 0.01 or more and 0.5 or less. <Aspect 6> 6. The negative electrode active material layer according to any one of aspects 1 to 5, wherein the amount of oxygen atoms in the silicon active material particles is 1.0% by mass or more and less than 5.0% by mass. Aspect 7 7. The negative electrode active material layer according to any one of aspects 1 to 6, wherein the silicon active material particles are silicon clathrate active material particles. <Aspect 8> A solid secondary battery having the negative electrode active material layer according to any one of aspects 1 to 7. Effect of the Invention

[0010] According to the present disclosure, it is possible to provide an anode active material layer in which the electrical conductivity of the silicon active material particles is improved by reducing the amount of oxygen atoms in the silicon active material particles, while the electrical resistance is not easily deteriorated even when the charging capacity of the battery is low (=low charging state), and a solid secondary battery having such an anode active material layer. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is an image obtained by observing a negative electrode active material layer with a scanning electron microscope (SEM) when the average particle size of the solid electrolyte particles is 0.1 μm (the ratio to the average particle size of the silicon active material particles is 0.083). [Diagram 2]FIG. 2 is an image obtained by observing the negative electrode active material layer with a scanning electron microscope (SEM) when the average particle size of the solid electrolyte particles is 1.1 μm (the ratio to the average particle size of the silicon active material particles is 0.92). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the present disclosure.

[0013] <Negative electrode active material layer> The negative electrode active material layer of the present disclosure contains silicon active material particles and solid electrolyte particles, in which the amount of oxygen atoms in the silicon active material particles is less than 5.0 mass %, and the solid electrolyte particles have an average particle size of 1.0 μm or less, and / or the ratio of the average particle size of the solid electrolyte particles to the average particle size of the silicon active material particles is 0.9 or less.

[0014] The present inventors have found that when the amount of oxygen atoms in the silicon active material particles is small, the problem of increased electrical resistance of the negative electrode active material layer during discharge becomes prominent.

[0015] The reason why this problem becomes prominent is presumed to be as follows, without intending to be bound by any theory: That is, silicon active material particles having a relatively large amount of oxygen atoms are relatively strongly bonded to each other by bonding with each other via silicon oxide portions, whereas silicon active material particles having a small amount of oxygen atoms are unlikely to form such relatively strong bonds, and as a result, when the silicon active material particles shrink, the contact state between the silicon active material particles is likely to deteriorate.

[0016] Furthermore, the present inventors have unexpectedly found that the above problems can be suppressed by reducing the average particle size of the solid electrolyte particles in the negative electrode active material layer or by reducing the ratio of the average particle size of the solid electrolyte particles to the average particle size of the silicon active material particles.

[0017] The reason for this is presumed to be as follows, without intending to be bound by any theory: By selecting the average particle size of the solid electrolyte particles as described above, it is possible to increase the number of interfaces between the silicon active material particles and the solid electrolyte particles and to reduce the number of interfaces between the silicon active material particles, thereby increasing the bonding strength between the particles contained in the negative electrode active material layer and suppressing the above-mentioned problems.

[0018] The negative electrode active material layer of the present disclosure comprises silicon active material particles, solid electrolyte particles, and optionally a conductive additive, and a binder.

[0019] The mass ratio of the silicon active material particles to the solid electrolyte particles in the negative electrode active material layer (mass of silicon active material particles: mass of solid electrolyte particles) is preferably 85:15 to 30:70, and more preferably 80:20 to 40:60.

[0020] The negative electrode active material layer may have a thickness of, for example, 0.1 to 1000 μm.

[0021] (Silicon active material particles) The amount of oxygen atoms in the silicon active material particles of the present disclosure is less than 5.0% by mass. This amount of oxygen atoms may be 4.5% by mass or less, 4.0% by mass or less, or 3.5% by mass or less. Such a small amount of oxygen atoms in the silicon active material particles may be preferable for improving the electrical conductivity in the silicon active material particles.

[0022] The amount of oxygen atoms in the silicon active material particles may be 0.5% by mass or more, 1.0% by mass or more, 1.5% by mass or more, 2.0% by mass or more, or 2.5% by mass or more. It may be preferable for the silicon active material particles to have oxygen atoms in order to promote bonding between the silicon active material particles.

[0023] The method of making the oxygen atom amount in the silicon active material particles less than 5.0 mass% is not particularly limited, but an example is a method of treating the surface of the silicon active material particles with a hydrogen halide such as hydrogen fluoride (HF). The silicon active material particles treated in this way may have a hydrogenated surface.

[0024] The method for quantifying the amount of oxygen atoms is not particularly limited, but an example is a method of calculating the amount from analytical values ​​obtained by elemental analysis using an oxygen-nitrogen-hydrogen (ONH) analyzer. Specifically, HORIBA's EMGA-pro can be used for this measurement.

[0025] The silicon active material particles of the present disclosure are preferably silicon clathrate active material particles, and more preferably type II silicon clathrate active material particles.

[0026] The average particle size of the silicon active material particles is not particularly limited, but may be, for example, 0.1 μm or more, 0.5 μm or more, or 1.0 μm or more. The average particle size of the silicon active material particles may be 10 μm or less, 8.0 μm or less, 6.0 μm or less, 4.0 μm or less, or 2.0 μm or less. In the present disclosure, the average particle size of the silicon active material particles can be determined, for example, as the average value of the circle area equivalent diameter of the silicon active material particles in a scanning electron microscope (SEM) image.

[0027] (Solid electrolyte particles) The material of the solid electrolyte particles is not particularly limited, and any material that can be used as a solid electrolyte for a solid secondary battery can be used. For example, the solid electrolyte particles may be a sulfide solid electrolyte, an oxide solid electrolyte, a polymer electrolyte, or the like, and is preferably a sulfide solid electrolyte.

[0028] Examples of sulfide solid electrolytes include, but are not limited to, sulfide amorphous solid electrolytes, sulfide crystalline solid electrolytes, and argyrodite-type solid electrolytes. Specific examples of sulfide solid electrolytes include Li2S-P2S5-based (Li7P3S 11, Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2 (Li 13 GeP3S 16 , Li 10 GeP2S 12 ), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x P.S. 6-x Cl x etc.; or combinations thereof, but are not limited to these.

[0029] An example of an oxide solid electrolyte is Li7La3Zr2O 12 , Li 7-x La3Zr 1-x Nb x O 12 , Li 7-3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3, Li 1+x Al x Ti 2-x (PO4)3, Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, or Li 3+x PO 4-x N x (LiPON), but is not limited to these.

[0030] The sulfide solid electrolyte and the oxide solid electrolyte may be glass or crystallized glass (glass ceramic).

[0031] Examples of the polymer electrolyte include, but are not limited to, polyethylene oxide (PEO), polypropylene oxide (PPO), and copolymers thereof.

[0032] The average particle size of the solid electrolyte particles may be 0.01 μm or more. The average particle size of the solid electrolyte particles may be 1.0 μm or less, 0.9 μm or less, 0.8 μm or less, 0.7 μm or less, 0.6 μm or less, or 0.5 μm or less. In the present disclosure, the average particle size of the solid electrolyte particles can be determined, for example, as the average value of the circle-area equivalent diameter of the solid electrolyte particles in a scanning electron microscope (SEM) image.

[0033] The ratio of the average particle size of the solid electrolyte particles to the average particle size of the silicon active material particles (particle size ratio) may be 0.9 or less, and may be 0.01 or more and 0.5 or less.

[0034] (Conductive assistant) The conductive additive is not particularly limited. For example, the conductive additive may be a carbon material such as VGCF (Vapor Grown Carbon Fiber) and carbon nanofiber, a metal material, or the like, but is not limited thereto.

[0035] (binder) The binder is not particularly limited. For example, the binder may be, but is not limited to, a material such as vinylidene fluoride (co)polymer, acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polytetrafluoroethylene (PTFE), or styrene butadiene rubber (SBR), or a combination thereof.

[0036] <Method for producing negative electrode active material layer> The disclosed method of producing an anode active material layer can include mixing silicon active material particles, solid electrolyte particles, and an organic solvent, and drying the slurry obtained by mixing.

[0037] For the silicon active material particles and the solid electrolyte particles, reference can be made to the above description regarding the negative electrode active material layer of the present disclosure.

[0038] Examples of the organic solvent include non-polar solvents such as heptane, xylene, and toluene, and polar solvents such as ester solvents, tertiary amine solvents, ether solvents, thiol solvents, and ketone solvents. The organic solvent is preferably a polar solvent, more preferably a ketone solvent, and even more preferably butyl butyrate.

[0039] <Solid secondary battery> The solid secondary battery of the present disclosure has the negative electrode active material layer of the present disclosure. The solid secondary battery of the present disclosure may have, in this order, a negative electrode current collector layer, a negative electrode active material layer of the present disclosure, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode current collector layer. Furthermore, the solid secondary battery of the present disclosure may be restrained by restraining members such as end plates from both sides in the stacking direction of each of the layers.

[0040] In the present disclosure, a "solid-state battery" refers to a battery that uses at least a solid electrolyte as an electrolyte, and therefore a solid-state battery may use a combination of a solid electrolyte and a liquid electrolyte as an electrolyte. Also, the solid-state battery of the present disclosure may be an all-solid-state battery, i.e., a battery that uses only a solid electrolyte as an electrolyte.

[0041] Since the solid secondary battery of the present disclosure has the negative electrode active material layer of the present disclosure, the amount of oxygen atoms in the silicon active material particles is reduced to improve the electrical conductivity of the silicon active material particles, while the electrical resistance is less likely to deteriorate even when the charging capacity of the battery is low (= low charging state).

[0042] (Negative electrode current collector layer) The material used for the negative electrode current collector layer is not particularly limited, and any material that can be used as a negative electrode current collector for a battery can be appropriately adopted. For example, the material may be stainless steel (SUS), aluminum, copper, nickel, iron, titanium, carbon, a resin current collector, or the like, but is not limited to these.

[0043] The shape of the negative electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.

[0044] (Negative electrode active material layer) For the negative electrode active material layer, reference can be made to the above description regarding the negative electrode active material layer of the present disclosure.

[0045] (Solid electrolyte layer) The solid electrolyte layer includes at least a solid electrolyte. In addition to the solid electrolyte, the solid electrolyte layer may include a binder, etc., as necessary. For the solid electrolyte and the binder, the above description regarding the negative electrode active material layer of the present disclosure can be referred to.

[0046] The solid electrolyte layer may be a layer impregnated with an electrolyte solution having lithium ion conductivity.

[0047] The electrolyte preferably contains an electrolyte supporting salt and a solvent. Examples of the electrolyte supporting salt (lithium salt) having lithium ion conductivity include inorganic lithium salts such as LiPF6, LiBF4, LiClO4, and LiAsF6, and organic lithium salts such as LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(FSO2)2, and LiC(CF3SO2)3. Examples of the solvent used in the electrolyte include cyclic esters (cyclic carbonates) such as ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC), and chain esters (chain carbonates) such as dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). The electrolyte preferably contains two or more solvents.

[0048] The thickness of the solid electrolyte layer is, for example, 0.1 to 1000 μm. The thickness of the solid electrolyte layer is preferably 0.1 to 300 μm, and particularly preferably 0.1 to 100 μm.

[0049] (Cathode active material layer) The positive electrode active material layer is a layer containing a positive electrode active material, and optionally a solid electrolyte, a conductive assistant, a binder, and the like.

[0050] In addition, when the positive electrode active material layer contains a solid electrolyte, the mass ratio of the positive electrode active material to the solid electrolyte in the positive electrode active material layer (mass of positive electrode active material: mass of solid electrolyte) is preferably 85:15 to 30:70, more preferably 80:20 to 40:60.

[0051] The material of the positive electrode active material is not particularly limited. For example, the positive electrode active material may be lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganate (LiMn2O4), LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Li 1+x Mn 2-x-y M y O4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni, and Zn), such as a hetero-element substituted Li-Mn spinel having a composition represented by the formula, but is not limited thereto.

[0052] The positive electrode active material can have a coating layer. The coating layer is a layer containing a substance having lithium ion conduction performance, low reactivity with the positive electrode active material and the solid electrolyte, and capable of maintaining the form of a coating layer that does not flow even when in contact with the active material and the solid electrolyte. Specific examples of the material constituting the coating layer include, in addition to LiNbO3, Li4Ti5O 12 , Li3PO4, Li 6-(4-x)b (Ti 1-x Al x ) b F6 (0 < x < 1, 0 < b ≤ 1.5), etc., but are not limited thereto.

[0053] Examples of the shape of the positive electrode active material include particulate. The average particle size (D50) of the positive electrode active material is not particularly limited, but is, for example, 10 nm or more, and may be 100 nm or more. On the other hand, the average particle size (D50) of the positive electrode active material is, for example, 50 μm or less, and may be 20 μm or less. The average particle size (D50) can be calculated, for example, from measurements using a laser diffraction particle size distribution analyzer or a scanning electron microscope (SEM).

[0054] For the solid electrolyte, the conductive assistant, and the binder, reference can be made to the above descriptions regarding the negative electrode active material layer of the present disclosure.

[0055] The thickness of the positive electrode active material layer is, for example, 0.1 μm or more and 1000 μm or less.

[0056] (Positive electrode current collector layer) The material and shape of the positive electrode current collector layer are not particularly limited, and the above description of the negative electrode active material layer of the present disclosure can be referred to. In particular, the material of the positive electrode current collector layer is preferably aluminum. The shape is preferably a foil. EXAMPLES

[0057] <<Preparation of solid-state secondary battery>> The solid secondary batteries of each example were fabricated as follows.

[0058] Preparation of Silicon Active Material Particles Example 1 A Si powder was prepared as a silicon (Si) source. This Si source and lithium (Li) metal were weighed out in a molar ratio of Li / Si=4.0 and mixed in a mortar in an argon atmosphere to obtain a lithium silicon (LiSi) alloy. The obtained LiSi alloy was reacted with ethanol in an argon atmosphere and treated with hydrogen fluoride (HF) to obtain a Si powder having voids inside the primary particles, i.e., a Si powder having a porous structure.

[0059] The obtained Si powder and sodium hydride (NaH) as a sodium (Na) source were used to produce a sodium silicon (NaSi) alloy. The NaH used was washed with hexane in advance. The Na source and the Si source were weighed out to a molar ratio of 1.05:1.00, and mixed using a cutter mill. The mixture was heated in a heating furnace under an argon atmosphere at 300°C for 60 hours to obtain a powdered NaSi alloy.

[0060] The obtained NaSi alloy was heated in an argon atmosphere at 270° C. for 120 hours to remove Na, thereby obtaining silicon active material particles of Example 1 having a clathrate II type crystal phase.

[0061] <Preparation of negative electrode laminate> 0.13g of multi-walled carbon nanotubes (MWCNT), 1g of silicon active material particles, 1.2g of sulfide solid electrolyte particles (average particle size 0.1μm), and 0.8g of 5wt% diisobutyl ketone solution of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) were added to 2.7g of diisobutyl ketone, and dispersed for 10 minutes with ultrasonic waves of 40μm amplitude and 20kHz frequency to obtain a negative electrode composite slurry. The obtained slurry was blade-coated on a roughened nickel (Ni) foil with a gap of 100μm, and dried for 30 minutes on a hot plate heated to 100℃ to form a negative electrode active material layer on the negative electrode current collector layer to obtain a negative electrode laminate.

[0062] (Preparation of solid electrolyte layer) 0.4g of sulfide solid electrolyte particles and 0.05g of 5wt% heptane solution of acrylonitrile butadiene rubber (ABR) were added to 0.8g of heptane, and dispersed by ultrasonic for 10 minutes to obtain a solid electrolyte slurry. The obtained slurry was applied to a stainless steel foil with a gap of 50μm, and dried for 30 minutes on a hot plate heated to 100℃ to form a solid electrolyte layer.

[0063] <Preparation of Positive Electrode Laminate> 2g of lithium nickel cobalt manganese oxide, 0.03g of multi-walled carbon nanotubes (MWCNT), 0.3g of sulfide solid electrolyte particles, and 0.3g of a 5wt% butyl butyrate solution of PVDF-HFP were added to 1g of butyl butyrate, and dispersed by ultrasonic waves for 10 minutes to obtain a positive electrode composite slurry. The obtained slurry was blade-coated on an aluminum (Al) foil with a gap of 100μm, and dried on a hot plate heated to 100℃ for 30 minutes to form a positive electrode active material layer on the positive electrode current collector layer, thereby obtaining a positive electrode laminate.

[0064] <Battery Assembly> The solid electrolyte layer was placed on the negative electrode laminate and roll-pressed at room temperature with a linear pressure of 3 t / cm. The solid electrolyte layer was placed on the positive electrode laminate and roll-pressed at 170°C with a linear pressure of 4 t / cm. 2 The solid electrolyte layers were then laminated and joined together to obtain a solid secondary battery.

[0065] Example 2 In producing the negative electrode laminate, the negative electrode active material layer of Example 2 was obtained in the same manner as in Example 1, except that solid electrolyte particles with an average particle size of 0.8 μm were used.

[0066] Comparative Example 1 In producing the negative electrode laminate, a negative electrode active material layer of Comparative Example 1 was obtained in the same manner as in Example 1, except that solid electrolyte particles with an average particle size of 1.1 μm were used.

[0067] Comparative Example 2 A negative electrode active material layer of Comparative Example 2 was obtained in the same manner as in Comparative Example 1, except that the HF treatment was not carried out in the preparation of the silicon active material particles.

[0068] Comparative Example 3 A negative electrode active material layer of Comparative Example 3 was obtained in the same manner as in Example 1, except that in producing the negative electrode laminate, solid electrolyte particles having an average particle size of 2.2 μm were used.

[0069] <evaluation> (oxygen atomic weight) The oxygen atomic weight was calculated from the analytical value by elemental analysis using an oxygen / nitrogen / hydrogen (ONH) analyzer (HORIBA, EMGA-pro).

[0070] (Average particle size) The average particle size was determined as the average value of the equivalent circular area diameter of the particles in a scanning electron microscope (SEM) image. The results are shown in Table 1.

[0071] (Electrical Resistance) The battery was charged at a rate of 1 / 10C to 4.35V by constant current constant voltage (CCCV), and then discharged at a rate of 1 / 3C to 3.35V by CCCV. It was then discharged at 7C, and the electrical resistance was calculated from the voltage change and current value over 10 seconds. The results are shown in Table 1.

[0072] (Confining pressure fluctuation) The amount of change in confining pressure was calculated by subtracting the initial confining pressure from the maximum load recorded by the load cell during the first charge, and dividing the result by the initial charge capacity. The results are shown in Table 1.

[0073] (electrode strength) The negative electrode laminate after densification is 1.2 cm 2 Punch out at 1.0cm 2 The negative electrode active material layer was pulled with a tensile tester until it broke, and the load at which it broke was taken as the electrode strength. The results are shown in Table 1.

[0074] [Table 1]

[0075] <result> As shown in Table 1, the batteries of the examples in which the oxygen atom concentration was within the range of the present disclosure for the average particle size of the solid electrolyte particles and the particle size ratio (average particle size of the solid electrolyte particles / average particle size of the silicon active material particles) had lower electrical resistance than the batteries of the comparative examples. In addition, the battery of Example 1 in which the average particle size of the solid electrolyte particles and the particle size ratio (average particle size of the solid electrolyte particles / average particle size of the silicon active material particles) were further reduced had higher electrode strength than the battery of Example 2.

Claims

1. Contains silicon active material particles and solid electrolyte particles, The amount of oxygen atoms in the silicon active material particles is less than 5.0% by mass, and The solid electrolyte particles have an average particle size of 0.01 μm or more and 0.7 μm or less. Negative electrode active material layer.

2. 2. The negative electrode active material layer according to claim 1, wherein the solid electrolyte particles have an average particle size of 0.01 μm or more and 0.5 μm or less.

3. Contains silicon active material particles and solid electrolyte particles, The amount of oxygen atoms in the silicon active material particles is less than 5.0% by mass, The average particle size of the silicon active material particles is 0.1 μm or more and 4.0 μm or less, and the solid electrolyte particles have an average particle size of 1.0 μm or less, and / or the ratio of the average particle size of the solid electrolyte particles to the average particle size of the silicon active material particles is 0.9 or less; Negative electrode active material layer.

4. The negative electrode active material layer according to claim 3 , wherein the solid electrolyte particles have an average particle size of 1.0 μm or less.

5. 4. The negative electrode active material layer according to claim 3, wherein a ratio of an average particle size of the solid electrolyte particles to an average particle size of the silicon active material particles is 0.9 or less.

6. 6. The negative electrode active material layer according to claim 5, wherein a ratio of an average particle size of the solid electrolyte particles to an average particle size of the silicon active material particles is 0.01 or more and 0.5 or less.

7. Contains silicon active material particles and solid electrolyte particles, The amount of oxygen atoms in the silicon active material particles is 1.0% by mass or more and less than 5.0% by mass, and the solid electrolyte particles have an average particle size of 1.0 μm or less, and / or the ratio of the average particle size of the solid electrolyte particles to the average particle size of the silicon active material particles is 0.9 or less; Negative electrode active material layer.

8. Contains silicon active material particles and solid electrolyte particles, The amount of oxygen atoms in the silicon active material particles is less than 5.0% by mass, The solid electrolyte particles have an average particle size of 1.0 μm or less, and / or the ratio of the average particle size of the solid electrolyte particles to the average particle size of the silicon active material particles is 0.9 or less; and The silicon active material particles are silicon clathrate active material particles. Negative electrode active material layer.

9. A solid secondary battery comprising the negative electrode active material layer according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Laminate battery

    JP2018190530A

  • All solid-state battery negative electrode and all solid lithium secondary battery

    JP2019179731A

  • All-solid battery negative electrode

    JP2021128857A

  • All-solid battery

    JP2022092723A

  • All-solid battery

    JP2022092725A